Emerging drugs for the treatment of hereditary angioedema due to C1-inhibitor deficiency. (3rd April 2022) - Zanichelli, Andrea; Montinaro, Vincenzo; Triggiani, Massimo; Arcoleo, Francesco; Visigalli, Debora; Cancian, Mauro
ABSTRACT: Introduction: Hereditary angioedema due to C1-inhibitor (C1-INH-HAE) is a rare disease characterized by unpredictable swelling attacks that may be life-threatening when affecting the upper airways. Understanding the pathophysiology of HAE and the mechanism of bradykinin-mediated angioedema allowed the development of new therapies for the treatment of HAE: clinical trials are ongoing to expand the number of drugs available for on-demand treatment and prophylaxis. Areas covered: Authors discuss the products that have been used to treat this disease for many years and present the most recently marketed products and those which are under development. Expert opinion: Significant therapeutic progress has been made in HAE. In particular, drugs targeting specific molecules involved in the angioedema formation were developed and studies with new drugs are ongoing. In the coming years, more effective therapies with easier administration route options for on-demand treatment and long-term prophylaxis will be available to treat this disease and the variety of patients. Gene therapy strategies may offer a definitive treatment. High costs of current and new drugs may be a limiting factor for their availability, especially in developing countries.